Analisis Faktor Determinan Kinerja Keuangan Dengan Komisaris Independen Sebagai Variabel Moderasi - Yanti Budiasih; Hendy Tannady; Ruki Ambar Arum; Paulus Laratmase; Umarudin Kurniawan (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study was to analyze the effect of capital intensity, capital structure, working capital turnover onfinancial performance moderated by independent commissioners. Capital intensity was measured using the capitalintensity ratio, capital structure was measured using the debt to equity ratio, working capital turnover was measuredusing working of capital turnover (WCTO), financial performance was measured using return on assets. Thepopulation used in this study uses companies listed in the food and beverage sector that are listed on the IDX in 2016-2020. The technique used in determining the sample is purposive sampling with a total of 105 observations. Theanalytical method used in this research is Moderate Regression Analysis (MRA). The hypothesis is accepted if theprobability value is 0.05. The results showed that capital intensity, capital structure and working capital turnover had noeffect on financial performance, independent commissioners did not moderate the effect of capital intensity, capitalstructure and working capital turnover on financial performance. Keywords: Capital Intensity, Capital Structure, Working Capital Turnover, Financial Performance, IndependentCommissioner